PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA (STUDI KASUS PUTUSAN NO 1793/PID.SUS/2020/PN.MKS) - Pramono Aji, Danang; Anita Sinaga, Niru (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Drug abuse in Indonesia is very complex. The author distinguishes between abuse and distribution of narcotics as stated in Decision No. 1793/Pid.Sus/2020/PN.Mks. The formulation of the problem in this study is 1) how is the regulation of drug abuse in Indonesia and 2) how is the application of criminal law based on Decision No. 1793/Pid.Sus/2020/PN.Mks? The aim is to find out the regulation of drug abuse in Indonesia and the application of criminal law based on Decision No. 1793/Pid.Sus/2020/PN.Mks. Using a normative legal research method, this study analyzes written laws from library materials or secondary data. The results of the study show that the regulation of drug abuse in Indonesia includes various laws and regulations, namely Article 111 paragraph (1) in conjunction with Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics and Article 127 paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics. In addition, the 2023 Criminal Code, Article 622 paragraph (15) also explicitly regulates criminal liability for perpetrators of drug abuse. Therefore, the Article in Law Number 35 of 2009 concerning Narcotics is declared invalid. In Decision No. 1793/Pid.Sus/2020/PN.Mks with the defendant Cakra Wira Darma alias Cakra bin Sudirman sentenced by the judge to 11 (Eleven) Months in prison, and the defendant underwent treatment and/or care through medical rehabilitation for 4 (Four) Months at the BNN Baddoka Rehabilitation Center, Makassar City. The Panel of Judges also determined that the length of time the defendant underwent treatment and/or care through medical rehabilitation was calculated as the period of serving the sentence.